2022
DOI: 10.3390/antibiotics11121768
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Highly Trimethoprim-Resistant DfrB Dihydrofolate Reductases in Diverse Environmental Settings Suggests an Evolutionary Advantage Unrelated to Antibiotic Resistance

Abstract: Type B dihydrofolate reductases (DfrB) are intrinsically highly resistant to the widely used antibiotic trimethoprim, posing a threat to global public health. The ten known DfrB family members have been strongly associated with genetic material related to the application of antibiotics. Several dfrB genes were associated with multidrug resistance contexts and mobile genetic elements, integrated both in chromosomes and plasmids. However, little is known regarding their presence in other environments. Here, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 47 publications
(75 reference statements)
2
10
0
Order By: Relevance
“…In contrast, the only conserved feature of the ∼20-residue, unstructured N-terminus of the DfrB protomer is its length. 15,23,44 Consistent with this, the creation of all possible point substitutions in the enzyme through a deep mutational scanning approach has demonstrated that substitutions in the SH3 core of DfrB1 are detrimental to the enzyme fitness, whereas the N-terminus is largely tolerant to sequence alteration. 45 Small-angle neutron scattering, MD simulations and 19 F NMR have determined that the N-terminus adopts a globally compact shape and interacts with Trp45 at the monomer–monomer interface, providing 2.6 kcal mol −1 of stability to the assembly.…”
Section: The First Step To Catalysis: Creation Of a Binding Scaffoldmentioning
confidence: 78%
See 4 more Smart Citations
“…In contrast, the only conserved feature of the ∼20-residue, unstructured N-terminus of the DfrB protomer is its length. 15,23,44 Consistent with this, the creation of all possible point substitutions in the enzyme through a deep mutational scanning approach has demonstrated that substitutions in the SH3 core of DfrB1 are detrimental to the enzyme fitness, whereas the N-terminus is largely tolerant to sequence alteration. 45 Small-angle neutron scattering, MD simulations and 19 F NMR have determined that the N-terminus adopts a globally compact shape and interacts with Trp45 at the monomer–monomer interface, providing 2.6 kcal mol −1 of stability to the assembly.…”
Section: The First Step To Catalysis: Creation Of a Binding Scaffoldmentioning
confidence: 78%
“…We therefore hypothesized that the DfrB in these environmental organisms were selected for a function other than to provide TMP resistance; whether they procure an evolutionary advantage by serving as an additional dihydrofolate reductase or have another, yet undiscovered function remains to be determined. 44…”
Section: When Catalysis Means Survival: the Emergence Of A Powerful A...mentioning
confidence: 99%
See 3 more Smart Citations